Feminism and Deconstruction - Dr Muhammad Abid (بازیافت)
Abstract Feminist sensibility viewed in circumference of Derridian philosophical acumen to deconstruction makes feminism a fluid, multiverse and multidextrous consciousness. Not that feminism is a term, theory or movement but that it is an event or occurrence and itself continues to deconstruct established feminist philosophy or praxis. According to deconstruction, feminist truth flows in multiplicity rather than being single or rigid.  Hence, deconstructionists raise a question against the sole connotation of feministic philosophy. The feminist discourse is an interdisciplinary one and shows facets of relative truth that has no end. In addition, Deconstruction discriminates the dichotomous categories of gender and sex, which suffice to femaleness but are incongruous to feminism. The present paper attempts to delineate feminism as a transitory event under flowing discourse of deconstruction.